Does photobiomodulation therapy enhance maximal muscle strength and muscle recovery? - Tsuk, S.; Lev, Y. H.; Fox, O.; Carasso, R.; Dunsky, A. (Journal of Human Kinetics, 2020)
Photobiomodulation has been shown to improve tissue and cell functions. We evaluated the influence of photobiomodulation, using a B-Cure laser, on: 1) maximal performance, and 2) muscle recovery after resistance exercise. Two separate crossover randomized double-blinded placebo-controlled trials were conducted. Sixty healthy physical education students (28 men, 32 women), aged 20-35, were recruited (30 participants for each trial). Participants performed two interventions for each experiment, with real lasers (GaAlAs, 808 nm) on three quadricep locations in parallel (overall treatment energy of ~150J) or sham (placebo) treatment. In the first experiment muscle total work (TW) and peak torque (PT) were measured by an isokinetic dynamometer in five repetitions of knee extension, and in the second experiment muscle recovery was measured after the induction of muscle fatigue by evaluating TW and PT in five repetitions of knee extension. There were no differences between treatments (real or sham) regarding the TW (F(1,28) = 1.09, p = .31), or PT (F(1,29) = .056, p = .814). In addition, there was no effect of photobiomodulation on muscle recovery as measured by the TW (F(1,27) = .16, p = .69) or PT (F(1,29) = .056, p = .814). Applying photobiomodulation for 10 min immediately before exercise did not improve muscle function or muscle recovery after fatigue.